Solusi Alternatif Mengatasi Paradok Pembangunan - Dedi Junaedi; Yanti Hasbian Setiawati (LPPM Institut Nasional Laa Roiba Bogor, 2019)
The aim of the research is to conduct a critical analysis of the paradox of development in Indonesia. from time to time, while looking for alternative solutions in the perspective of Islamic economic thought. This study is to answer the problem: Why does the megadiversity that is owned do not provide welfare and prosperity for most of its citizens. Why natural wealth has not given much blessing and benefit; What and how Islamic economic thought answers the issue. The research method used is qualitative descriptive analysis and tracking of Islamic economic literacy. The data used is a combination of primary and secondary data from various reference sources: books, journals and printed and online mass media literacy. The results of the study show that from year to year, in the alternation of the ruling political regime, the Indonesian economy grew positively. Statistically, the value of our Gross Domestic Product (GDP) continues to increase. Even so per capita income always rises from time to time. However, there are still dozens of Indonesians who are still classified as poor. Improved economic growth after the global economic crisis did not provide prosperity, justice and benefit evenly. The gap is still wide open between rich-poor, city-area, West-East region. This happened because there was something wrong in the management of natural resources, the corrupt behavior of state and regional administrators, the unequal development between Java and outside Java, between the West and the East, the dominance of foreign capitalist companies, the optimal excavation and management of ZISWAF, and still not yet grounded the application of Islamic economics in Indonesia. So, to get out of the problem and improve from the chronic problem, six strategic steps are needed: (1) to eradicate KKN indiscriminately in all SOEs and government bureaucracy; (2) improvements in the management of the country's wealth resources; (3) it is necessary to design policies and budgets to accelerate poverty and inequality reduction, by allocating more funds to projects that absorb a lot; (4) reviewing policies that are not pro-people; (5) optimizing and maximizing the excavation and management of zakat, infaq, alms and endowments (ZISWAF); (6) facilitating Islamic economic and financial growth. Keywords: development paradigm, growth, poverty, Islamic economy, people's welfare.